LEVEL OF DIETARY COMPLIANCE AMONG HYPERTENSION PATIENTS AT IBNU SINA GRESIK REGIONAL GENERAL HOSPITAL - Purwanto, Cucuk Rahmadi; Illmy Muhalla, Hafna; Tiara Efendi, Rani (Journal of Vocational Nursing, 2024)
Introduction: Hypertension is a prevalent chronic disease among adults worldwide, including in Indonesia. A busy lifestyle and tight routine are some of the reasons why someone does not adhere to hypertension therapy or ignores a healthy lifestyle, such as consuming junk food that is high in fat and sugar, having an irregular activity pattern, and having irregular activity patterns. This study aimed to describe the dietary compliance of hypertensive patients. Methods: The research was conducted using a descriptive design, with the population comprising hypertensive patients, and a sample of 45 respondents selected through accidental sampling. The variable studied was the level of dietary compliance. The inclusion criteria were patients registered at the heart polyclinic and willing to be studied, while the exclusion criteria were suffering from mental disorders or severe complications such as stage 5 chronic kidney failure. The instrument used was the Dietary Approaches to Stop Hypertension (DASH) diet compliance questionnaire administered in June 2023. Results: The results indicated that 42.2% of respondents were compliant, 42.2% were moderately compliant, and 15.6% were non-compliant. The conclusion was that nearly half of the respondents adhered to the hypertension diet. Conclusions: It is hoped that nurses can provide Communication, Information, and Education (IEC) to hypertensive patients through comprehensive counseling on hypertension management, emphasizing the importance of adhering to a hypertension diet, antihypertensive therapy, and other healthy lifestyle modifications such as physical activity and smoking cessation, and involving families in improving compliance with the DASH diet.